2015
DOI: 10.1007/s10726-015-9456-4
|View full text |Cite
|
Sign up to set email alerts
|

The Accounting Court: Some Speculations on Why Not?

Abstract: The accounting court proposed by Spacek (Account Rev 33(3):368, 1958) was a potent and controversial idea. The court would provide a venue to which auditing firms and clients could bring disputes over the application of accounting principles and over time would build a database of casework illustrating the court's decisions on proper application and interpretation of accounting principles. In this paper, we contribute to the literature on the accounting court and on standard setting by analyzing group value or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Other theoretical papers suggested that auditors' failure to discover fraud pertains to the audit profession's reluctance to accept responsibility for fraudulent financial reporting detection (Reinstein and McMillan, 2004). It may also be attributable to mistakes around the audit process, auditor inherent factors, institutional factors and morality (Kleinman et al, 2020). Emphasising the significance of morality, Morales-S anchez et al (2020) discuss that promoting the ethical behaviours of auditors improves audit quality.…”
Section: Slr Insights and Gapsmentioning
confidence: 99%
“…Other theoretical papers suggested that auditors' failure to discover fraud pertains to the audit profession's reluctance to accept responsibility for fraudulent financial reporting detection (Reinstein and McMillan, 2004). It may also be attributable to mistakes around the audit process, auditor inherent factors, institutional factors and morality (Kleinman et al, 2020). Emphasising the significance of morality, Morales-S anchez et al (2020) discuss that promoting the ethical behaviours of auditors improves audit quality.…”
Section: Slr Insights and Gapsmentioning
confidence: 99%
“…The auditor, the audit team and the responsible partner obtain audit evidence from customer management records, reports and other areas that provide a basis for determining audit results (Kleinman et al , 2020). The auditor’s interaction with the client or the audited company and trusting them is one of the basic strategies for gathering appropriate evidence (PCAOB, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is difficult to maintain trust and confidence (Barlaup et al , 2009) because the behaviors of complex people and the detection of immoral behaviors have also become more complex. Kleinman et al (2020) argue that ethical philosophies are behavioral principles that usually influence decision-making; hence, auditors are expected to express different behaviors and attitudes in the face of the environmental conditions of companies and the ethical framework because the auditor’s decisions and audit results also depend on their feelings, beliefs or knowledge and ethical and ideological factors that the auditor possesses, which may cause the auditor to fail to identify signs of fraud (Murphy and Dacin, 2011; Trompeter et al , 2013). Also, ethical issues in the management and scandals of business units in the past few years, which are caused by their unethical behavior, have never been far from the news headlines around the world, which have a contrarious impact in the short term (Conway and Kotera, 2020) and long term (Crane and Matten, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the auditor performs audit responsibilities through the knowledge created through experience, training and personal characteristics and experiences. Auditors' failure to detect fraud may be influenced by individual and group bias, personal and professional experience, confusion, prejudice, expectations, peer pressure and ability and risk-taking (Kleinman et al 2012;Kleinman et al 2020). Besides, the failures of auditors may be derived from the characteristics of the audited company, which can be attributed to non-compliance with ethical principles in business.…”
Section: Introductionmentioning
confidence: 99%